1992
DOI: 10.1346/ccmn.1992.0400315
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectra of Soil Kaolins from South-Western Australia

Abstract: Abstract--Six well-characterized soil kaolins from widely separated sites in south-western Australia and four reference kaolins were studied by 57Fe M6ssbauer spectroscopy at room temperature after removal of non-structurally-bound iron with dithionite-citrate-bicarbonate solution. The soil kaolins and one of the reference kaolins were also studied at temperatures near 16 K. The soil kaolins were remarkably similar in crystal size, crystaUinity, dehydroxylation temperature, cation exchange capacity, surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…Kaolinite was also highlighted. It is reported that this clay may contain some amount of iron (Murad, 2010;Saint Pierre et al, 1992;Stevens et al, 2005). Yet, this amount remains low as the substitution of Al by Fe is weak (<2%) to nil (Murad, 1998) whereas illite already contains from 1% to 8% of iron (Murad, 1998).…”
Section: The Speciation Of Iron In Shalementioning
confidence: 98%
See 2 more Smart Citations
“…Kaolinite was also highlighted. It is reported that this clay may contain some amount of iron (Murad, 2010;Saint Pierre et al, 1992;Stevens et al, 2005). Yet, this amount remains low as the substitution of Al by Fe is weak (<2%) to nil (Murad, 1998) whereas illite already contains from 1% to 8% of iron (Murad, 1998).…”
Section: The Speciation Of Iron In Shalementioning
confidence: 98%
“…Paramètres Mössbauer mesurés sur les échantillons de schistes argileux et trouvés dans la littérature. Liste des références (Dyar et al, 2013 ;Ferrow, 2002 ;Huffman et Huggins, 1978 ;Loayza et al, 2011 ;Medina et al, 2006 ;Olowe et Genin, 1991 ;Pysh'yev et al, 2004 ;Saint Pierre et al, 1992 ;Stevens et al, 2005 ;Verma et Tripathi, 2000 ;Wagner et Wagner, 2004).…”
Section: Tableunclassified
See 1 more Smart Citation
“…7a) [the firing product of kaolinite, metakaolin, is known to give very weak XRD peaks (Murad & Wagner 1991)]. The parameters of the high‐spin Fe(II) Mössbauer signal from the unheated sample are consistent with those for Fe(II) bound within the kaolinite lattice (Murad & Wagner 1991; Malden & Meads 1967; Cuttler 1980; St. Pierre et al . 1992).…”
Section: Mineralogical Explanation For the Magnetic Changes By Heatingmentioning
confidence: 77%
“…Previous studies recognized differences in the morphology and composition of kaolinite in different environments. Large, well crystallized kaolinite occurs in epithermal and geothermal environments (Dill et al, 1997;Simpson et al, 2001;Tillick et al, 2001;Mas et al, 2003) and in saprolite underlying kaolin deposits (Varajão et al, 2001), whereas small crystals of disordered, Fe-substituted kaolinite occur in tropical soils (Herbillon et al, 1976;St Pierre et al, 1992;Hart et al, 2002Hart et al, , 2003. Both crystal morphology and composition were used by Dill et al (1997) to distinguish hypogene kaolinite associated with argillic alteration in an epithermal setting from supergene kaolinite formed by weathering, the former being more ordered and containing less Fe and Ti.…”
Section: Introductionmentioning
confidence: 99%